Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Para factorizar [tex]\(8x^3 + 27\)[/tex], seguimos estos pasos:
1. Identificar la expresión dada: La expresión es [tex]\(8x^3 + 27\)[/tex].
2. Reconocer la suma de cubos: La expresión [tex]\(8x^3 + 27\)[/tex] puede ser reconocida como una suma de cubos, ya que [tex]\(8x^3 = (2x)^3\)[/tex] y [tex]\(27 = 3^3\)[/tex]. La forma general de la factorización de la suma de cubos [tex]\(a^3 + b^3\)[/tex] es:
[tex]\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \][/tex]
3. Asignar valores a [tex]\(a\)[/tex] y [tex]\(b\)[/tex]:
- Aquí, [tex]\(a = 2x\)[/tex] y [tex]\(b = 3\)[/tex].
4. Escribir la forma factorizada: Usando los valores de [tex]\(a\)[/tex] y [tex]\(b\)[/tex], se puede escribir la forma factorizada de [tex]\(8x^3 + 27\)[/tex] como:
[tex]\[ (2x + 3)((2x)^2 - (2x)(3) + 3^2) \][/tex]
5. Simplificar dentro de los paréntesis:
- [tex]\((2x)^2 = 4x^2\)[/tex]
- [tex]\((2x)(3) = 6x\)[/tex]
- [tex]\(3^2 = 9\)[/tex]
Entonces, la factorización se vuelve:
[tex]\[ (2x + 3)(4x^2 - 6x + 9) \][/tex]
6. Identificar los coeficientes: A partir de la forma factorizada [tex]\((2x + 3)(4x^2 - 6x + 9)\)[/tex], podemos identificar:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = 4\)[/tex]
- [tex]\(d = 6\)[/tex]
- [tex]\(e = 9\)[/tex]
7. Calcular [tex]\(a + b + c - d + e\)[/tex]:
[tex]\[ a + b + c - d + e = 2 + 3 + 4 - 6 + 9 \][/tex]
8. Realizar la suma:
[tex]\[ 2 + 3 + 4 = 9 \][/tex]
[tex]\[ 9 - 6 = 3 \][/tex]
[tex]\[ 3 + 9 = 12 \][/tex]
Por lo tanto, el valor de [tex]\(a + b + c - d + e\)[/tex] es [tex]\(12\)[/tex].
1. Identificar la expresión dada: La expresión es [tex]\(8x^3 + 27\)[/tex].
2. Reconocer la suma de cubos: La expresión [tex]\(8x^3 + 27\)[/tex] puede ser reconocida como una suma de cubos, ya que [tex]\(8x^3 = (2x)^3\)[/tex] y [tex]\(27 = 3^3\)[/tex]. La forma general de la factorización de la suma de cubos [tex]\(a^3 + b^3\)[/tex] es:
[tex]\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \][/tex]
3. Asignar valores a [tex]\(a\)[/tex] y [tex]\(b\)[/tex]:
- Aquí, [tex]\(a = 2x\)[/tex] y [tex]\(b = 3\)[/tex].
4. Escribir la forma factorizada: Usando los valores de [tex]\(a\)[/tex] y [tex]\(b\)[/tex], se puede escribir la forma factorizada de [tex]\(8x^3 + 27\)[/tex] como:
[tex]\[ (2x + 3)((2x)^2 - (2x)(3) + 3^2) \][/tex]
5. Simplificar dentro de los paréntesis:
- [tex]\((2x)^2 = 4x^2\)[/tex]
- [tex]\((2x)(3) = 6x\)[/tex]
- [tex]\(3^2 = 9\)[/tex]
Entonces, la factorización se vuelve:
[tex]\[ (2x + 3)(4x^2 - 6x + 9) \][/tex]
6. Identificar los coeficientes: A partir de la forma factorizada [tex]\((2x + 3)(4x^2 - 6x + 9)\)[/tex], podemos identificar:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = 4\)[/tex]
- [tex]\(d = 6\)[/tex]
- [tex]\(e = 9\)[/tex]
7. Calcular [tex]\(a + b + c - d + e\)[/tex]:
[tex]\[ a + b + c - d + e = 2 + 3 + 4 - 6 + 9 \][/tex]
8. Realizar la suma:
[tex]\[ 2 + 3 + 4 = 9 \][/tex]
[tex]\[ 9 - 6 = 3 \][/tex]
[tex]\[ 3 + 9 = 12 \][/tex]
Por lo tanto, el valor de [tex]\(a + b + c - d + e\)[/tex] es [tex]\(12\)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.